Pneumococcal carriage in a large Sicilian sample population: impact on the current epidemiological scenario and implications for future vaccination strategies - Emanuele Amodio; Fabio Tramuto; Fabio Tramuto; Valerio De Francisci; Dario Genovese; Valeria Guzzetta; Vincenzo Pisciotta; Arianna Santino; Giulia Randazzo; Giulio Trapani; Giuseppe Vella; Francesco Vitale; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionStreptococcus pneumoniae is a prevalent and virulent global pathogen, with colonization being considered a precondition for pneumococcal disease. Understanding colonization is critical for gaining insights into transmission dynamics and developing effective interventions. This study aimed to determine the prevalence of nasopharyngeal colonization and serotype distribution in the Sicilian population.MethodsObservational study randomly selecting samples belonging to Sicilian individuals whose nasopharyngeal swabs were collected between February 1, 2020, and December 31, 2022. Pneumococcal colonization was determined using PCR for the pneumococcal autolysin (LytA) gene, and positive samples were serotyped.ResultsThe study sample consisted of 1,196 individuals, with 17.4% testing positive for the LytA gene. Pneumococcal colonization rates fell from birth to 24 years, with a peak in 0-4-year-olds (aOR=6.9; p<0.001). Colonization was higher in colder months, particularly in December (aOR=2.9, p<0.05) and February (aOR=4, p<0.05). Serotypes 22F and 24ABF exhibited strong colonization and an invasive pneumococcal disease (IPD) risk, whereas serotypes 4, 6AB, 9VA, and 13 had high colonization but a low IPD risk. Serotypes 3 and 8 exhibited considerable IPD risk but low colonization.ConclusionOur findings provide insights into pneumococcal colonization mechanisms, influencing serotype prevalence, colonization risk variables, and serotype comparisons for colonization and pathogenicity propensity.